Violation of the Engineer's Code of Ethics in Recruiting Welder Qualifications Project PLTM Parmonangan - Rijal S. Simanungkalit; Eka Daryanto (International Journal of Science and Environment (IJSE), 2026)
The Engineering Profession carries high moral and legal responsibilities, and is obligated to adhere to the Indonesian Engineers Code of Ethics (KEII) to prioritize public safety. This mini-research examines the dilemma of Engineer integrity during the qualification process of welders for high-pressure pipeline (penstock) installations at the Parmonangan Mini-hydro Power Plant (PLTM) Project. Pressure from project management regarding cost and schedule potentially drives ethical compromises that endanger construction quality and operational safety. This research uses a Descriptive-Analytical Qualitative Case Study approach. Data was collected through a triangulation of findings from interviews with the Project Engineer, analysis of qualification documents, and field observation (Non-Destructive Testing/NDT results) at the Parmonangan PLTM Project. A critical technical gap was found: the project mandated 5G/6G welder qualification (ASME/AWS) for the penstock, yet the Project Engineer accepted welders with a lower 3G qualification, driven by cost and schedule pressures. This practice resulted in a high incidence of weld defects (e.g., porosity and undercut) requiring repair. This compromise was proven to violate fundamental points of the KEII: Mandate 1 (Public Safety): The decision to accept non-competent welders increased the risk of penstock failure, threatening public safety. Mandate 3 (Competence): The Engineer approved work that was technically unjustifiable according to standards. Mandate 6 (Professional Integrity): The Engineer failed to avoid a conflict of interest between ethical obligations and commercial interests. The practice of accepting welders with inadequate qualifications at the Parmonangan PLTM Project constitutes a fundamental violation of the KEII caused by business pressures. This not only diminishes construction quality but also potentially leads to long-term technical consequences, namely reduced integrity and service life of the facility. It is necessary for the Project Owner to affirm quality and safety as non-negotiable criteria. Furthermore, the Indonesian Engineers Association (PII) must strengthen mechanisms for professional protection for Engineers who reject management policies that violate the code of ethics and technical standards.